The Challenge of Climate Change to Rural Dwellers in Esanland - Ola, Temitope Peter (International Journal of Humanities and Social Science Research, 2018)
The study appraises the effects of climate change on rural dwellers in Esanland, Edo State, Nigeria. It investigates how the rural dwellers in Esanland perceive climate change. This is to deepen the understanding of the rural dwellers’ awareness and vulnerability to climate change. The study uses primary and secondary data. Primary data is obtained through the administration of the structured questionnaire, conduct of in-depth interviews and field observation. The secondary data is sourced from textbooks, journals, conference proceedings, and publications of relevant government agencies. Descriptive method of data analysis is utilized to analyze the data. The results show that climate change has resulted in reduced soil fertility and food production; distorted the eco-system as well as induced health challenges among rural dwellers in Esanland. The study concludes that though there is a general awareness of climate change among rural dwellers in Esanland the area are still very much venerable to the adverse effects of climate change because of inadequate information, lack of finance among others.